2002
DOI: 10.1038/sj.hdy.6800156
|View full text |Cite
|
Sign up to set email alerts
|

Cacao domestication I: the origin of the cacao cultivated by the Mayas

Abstract: Criollo cacao (Theobroma cacao ssp. cacao) was cultivated by the Mayas over 1500 years ago. It has been suggested that Criollo cacao originated in Central America and that it evolved independently from the cacao populations in the Amazon basin. Cacao populations from the Amazon basin are included in the second morphogeographic group: Forastero, and assigned to T. cacao ssp. sphaerocarpum. To gain further insight into the origin and genetic basis of Criollo cacao from Central America, RFLP and microsatellite an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
230
0
23

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(282 citation statements)
references
References 25 publications
(28 reference statements)
18
230
0
23
Order By: Relevance
“…Researchers have focused on the natural distribution of the cacao tree (Theobroma cacao L.) within tropical regions of South America and Mesoamerica (2). Scholars also have emphasized the geographical areas of domestication (2)(3)(4), and recent research on the botanical origins and domestication of cacao in South America has focused on the western headwaters region of the Amazon basin in the geographical vicinity of northwestern Colombia (2). Currently, there is no evidence to suggest that early inhabitants of this South American region prepared chocolate in the strict sense.…”
Section: Previous Researchmentioning
confidence: 99%
“…Researchers have focused on the natural distribution of the cacao tree (Theobroma cacao L.) within tropical regions of South America and Mesoamerica (2). Scholars also have emphasized the geographical areas of domestication (2)(3)(4), and recent research on the botanical origins and domestication of cacao in South America has focused on the western headwaters region of the Amazon basin in the geographical vicinity of northwestern Colombia (2). Currently, there is no evidence to suggest that early inhabitants of this South American region prepared chocolate in the strict sense.…”
Section: Previous Researchmentioning
confidence: 99%
“…The putative centre of T. cacao diversity was originally hypothesised to be located in the region between Ecuador, Colombia and Peru (Cheesman, 1944) and was later confirmed by a microsatellite marker analysis (Motamayor et al, 2002(Motamayor et al, , 2008. Despite the importance of this plant, little is known about the natural genetic structure of the T. cacao population because most studies have utilised accessions that were originally collected in the wild, but maintained in ex situ germplasm repositories.…”
Section: Introductionmentioning
confidence: 99%
“…Under natural conditions the tree can reach 20 to 25 m in height (Lachenaud et al, 1997), whereas under cultivation it varies from 3 to 5 m. The geographical origin of cacao is South America (Motamayor et al, 2002), where several wild populations can be found in the Amazon and Guyanian regions. It is considered one of the most important perennial crops in the planet, with an estimated world output of 3.5 millions tons in (ICCO, 2007.…”
Section: Introductionmentioning
confidence: 99%